2016
DOI: 10.1002/2016ja022702
|View full text |Cite
|
Sign up to set email alerts
|

The spectroscopy of individual terrestrial gamma‐ray flashes: Constraining the source properties

Abstract: We report on the spectral analysis of individual terrestrial gamma‐ray flashes (TGFs) observed with the Fermi Gamma‐ray Burst Monitor (GBM). The large GBM TGF sample provides 46 events suitable for individual spectral analysis: sufficiently bright, localized by ground‐based radio, and with the gamma rays reaching a detector unobstructed. These TGFs exhibit diverse spectral characteristics that are hidden when using summed analysis methods. We account for the low counts in individual TGFs by using Poisson likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
140
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(157 citation statements)
references
References 51 publications
16
140
1
Order By: Relevance
“…Gjesteland et al (2015) analyzed three bright TGFs observed by the Reuven Ramaty High Energy Solar Spectroscopic Imager above the Mediterranean Sea region. Mailyan et al (2016) found that several events were best fit by wide geometry beams, while some other events were best fit by narrow beams. More recently, Mailyan et al (2016) have done a spectral analysis of more than 40 events observed by the Gamma-ray Burst Monitor (GBM) on-board the Fermi spacecraft (Meegan et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Gjesteland et al (2015) analyzed three bright TGFs observed by the Reuven Ramaty High Energy Solar Spectroscopic Imager above the Mediterranean Sea region. Mailyan et al (2016) found that several events were best fit by wide geometry beams, while some other events were best fit by narrow beams. More recently, Mailyan et al (2016) have done a spectral analysis of more than 40 events observed by the Gamma-ray Burst Monitor (GBM) on-board the Fermi spacecraft (Meegan et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…The likelihood analysis showed that the individual spectra are diverse and that different TGF events are best fit by various While analyzing the TGF data, care should be taken to account for spectral distortions caused by the pulse pileup, as those instrumental effects play an important role for TGFs with high photon rates. There were some indications of TGF producing beams being tilted from satellite TGF measurements as well Mailyan et al, 2016). Mailyan et al (2016) found that several events were best fit by wide geometry beams, while some other events were best fit by narrow beams.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…NaI detectors have a high rate of overflow counts, making TGF spectra obtained from them very hard to analyse in practice. On the other hand, these problems are less important for the BGO detectors, allowing correction and study of spectra from single TGF events (Mailyan et al, 2016).…”
Section: Tgf Detection Performancementioning
confidence: 99%